PELATIHAN FARM RECORD DAN EVALUASI RESIKO USAHA TANI UNTUK PENINGKATAN KOMPETENSI PETANI MANDIRI - Eva Dolorosa; Dewi Kuniati; Joshua Hutajulu H.; Nurliza (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
The focus of PKM is the "Sumber Lestari" farmer group in Rasau Jaya Village, which is a transmigration area as the Integrated Integrated Zone. Still, farmers in farmer groups do not have farm record so that the difficulty in managing and making optimal farming decisions. This condition is caused by low performance of farmers' skills and risk of farming competencies. Furthermore, farmer groups are only intuitively emphasizing the cost of agricultural production inputs for the most effective farming decisions because of the absence of farm records. Therefore, PKM is tried to give knowledge and training of farm record and farming risk evaluation to achieve the optimal of farming management. The results are shown that the effectiveness ratio is quite effective so that there is still a gap between knowledge and skills that must be followed by the role of local government through continuous monitoring and guidance on the development of processed products to increase the income of surrounding farmers